A Comparative Analysis of Biodegradation and Bioconversion of Lentinula edodes and Other Exotic Mushrooms - Zied, Diego Cunha [UNESP]; da Silva Freitas, Marcos Antônio [UNESP]; de Almeida Moreira, Bruno Rafael [UNESP]; da Silva Alves, Lucas [UNESP]; Pardo-Giménez, Arturo (MDPI, 2023)
Mushrooms are capable of bioconverting organic residues into food. Understanding the relationship between high-quality yields and substrate biomass from these residues is critical for mushroom farms when choosing new strains. The objective of this exploratory study was, therefore, to analyze whether exotic mushrooms, namely, Pleurotus eryngii, Flammulina velutipes, and Agrocybe aegerita, could biologically convert the substrate into edible mushrooms as effectively as Lentinula edodes (baseline). Five experiments were carried out. Biological efficiency, biodegradability coefficient, mass balance and chemical characterization of the substrate were evaluated. Strategically hydrating the sawdust enabled L. edodes to achieve the greatest biodegradability and biological efficiency of 0.5 and 94.2 kg dt−1, respectively. The values for L. edodes on wheat straw without hydration were 0.2 and 68.8 kg dt−1, respectively. From 1000 kg of fresh substrate, P. eryngii produced 150.1 kg of edible mushrooms, making it technically competitive with L. edodes on wheat straw (195.9 kg). Hence, P. eryngii was the most reliable option for scaling among the exotic mushrooms. The analytical insights from our study provide further knowledge to advance the field’s prominence in high-throughput mushroom-producing systems, particularly for exotic mushrooms.
Keywords: Agrocybe aegerita; Flammulina velutipes; Pleurotus eryngii; shiitake